Dois Pesos, duas medidas: Confiança seletiva e discriminação por biotipo em crianças pré-escolares - Messias, Ana Carolina (Universidade Federal de São Carlos, 2025)
Children do not trust indiscriminately when facing two possible informants; they select the one they find is the best one based on criteria that can be epistemic or not. Considering recent findings that suggest children prefer more attractive informants in selective trust tasks, studies investigating the role of perception of informants’ different physical attributes may contribute to the advancement of this field of studies. The main goal of the present work was to investigate whether 3 to 5-year-olds select whom to trust based on their body type (slim or fat) in novel learning situations. The present work encompasses two studies: a pilot study and a cross-cultural experimental study with Brazilian and U.S. children. The pilot study was conducted online with 7 Brazilian children (M= 54.9 months, SD = 6.96 months). This study aimed to test the classic selective trust paradigm in Brazilian children by manipulating accuracy history and informants' body type. Additionally, the researcher was interested in investigating whether 4 and 5-year-olds prefer a slim informant or one who has been accurate in the past. An adapted Selective Trust Task contrasted two potential female informants (one with a fat body type and one with a slim body type). The task consisted in presenting a video on an online video chat platform. Results demonstrated that participants preferred the accurate informant regardless of her body type. However, when both informants had the same history of reliability, children preferred the slim informant. These findings also revealed the need for some procedure modifications (e.g., not to provide information about the informants' history). Those changes were incorporated in a subsequent experimental study conducted with 50 US children (M= 52 months SD= 6.65 months) and 49 Brazilian children (M= 54 months SD= 10.36 months). For this study, three measures were used: the modified version of the selective trust task, one instrument to assess children’s body image and one scale to map children’s attitudes toward the fat and slim body types. The Selective Trust Task involved the presentation of four unfamiliar objects (one per trial) and four pairs of informants (one per trial). Two pairs of informants were females, and two pairs were males. Each pair was formed by a thin and a fat person. Children should select one of the informants of each pair presented to ask for help with the name of the object, and endorse a label given by one of them. The primary findings indicated that 61% of Brazilian children and 46% of U.S. children preferred the thin informants in the "ask" trials. Similarly, 51% of Brazilian children and 46% of U.S. children selected the thin informants in the "endorse" trials. Additionally, 57.2% of Brazilian participants and 40% of U.S. participants favored the thin informant in the explicit judgment task. These results suggest that children from both countries consistently exhibited a preference for thin informants across the four selective trust trials, indicating a negative bias against fat body types in both cultures. Also, no significant associations were found between the selective trust task scores and the attitudes and body type scale results. However, Brazilian children displayed a less negative attitude toward fat body types compared to U.S. children. Furthermore, an age-related trend was observed, with older children exhibiting a stronger negative bias against fat body types.
Selective trust and body type discrimination in preschoolers
Keywords: Confiança seletiva; Aprendizagem pelo testemunho; Biotipo; Crianças pré-escolares; Selective trust; Testimonial learning; Body type; Preschoolers; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; 5. Igualdade de Gênero; 10. Redução das Desigualdades